Two distinct microbial communities revealed in the sponge Cinachyrella - Cuvelier, Marie L.; Blake, Emily; Mulheron, Rebecca; McCarthy, Peter J.; Blackwelder, Patricia; Thurber, Rebecca L. Vega; Lopez, Jose V. (Frontiers in Microbiology, 2014)
Marine sponges are vital components of benthic and coral reef ecosystems, providing shelter and nutrition for many organisms. In addition, sponges act as an essential carbon and nutrient link between the pelagic and benthic environment by filtering large quantities of seawater. Many sponge species harbor a diverse microbial community (including Archaea, Bacteria and Eukaryotes), which can constitute up to 50% of the sponge biomass. Sponges of the genus Cinachyrella are common in Caribbean and Floridian reefs and their archaeal and bacterial microbiomes were explored here using 16S rDNA tag pyrosequencing. Cinachyrella specimens and seawater samples were collected from the same South Florida reef at two different times of year. In total, 639 OTUs (12 archaeal and 627 bacterial) belonging to 2 archaeal and 21 bacterial phyla were detected in the sponges. Based on their microbiomes, the six sponge samples formed two distinct groups, namely sponge group 1 (SG1) with low diversity (Shannon-Weiner index: 3.73 ± 0.22) and SG2 with higher diversity (Shannon-Weiner index: 5.95 ± 0.25). Hosts’ 28S rDNA sequences further confirmed that the sponge specimens were composed of two taxa closely related to Cinachyrella kuekenthalli. Both sponge groups were dominated by Proteobacteria, but Alphaproteobacteria were significantly more abundant in SG1. SG2 harbored many bacterial phyla (>1% of sequences) present in low abundance or below detection limits (<0.07%) in SG1 including: Acidobacteria, Chloroflexi, Gemmatimonadetes, Nitrospirae, PAUC34f, Poribacteria and Verrucomicrobia. Furthermore, SG1 and SG2 only had 95 OTUs in common, representing 30.5% and 22.4% of SG1 and SG2’s total OTUs, respectively. These results suggest that the sponge host may exert a pivotal influence on the nature and structure of the microbial community and may only be marginally affected by external environment parameters.